INTEGRATED WEED MANGEMENT PRACTICES FOR IMPROVED PRODUCTIVITY AND ECONOMICS IN MUNGBEAN (Vigna radiata (L.) - P. VENKATA RAO, A. SUBBARAMI REDDY, J.SATEESH BABU and M.V. RAMANA (The Journal of Research ANGRAU, 2023)
A field experiment was conducted during kharif seasons of 2013 and 2014 at RARS, Guntur on deep black clay loam soil to study the effect of integrated weed management practices for improved productivity and economics of mungbean. The experiment was laid out with nine weed control treatments. The maximum yield attributes, grain yield, gross returns, net returns and effective weed control in mungbean were recorded with pre-emergence application of Pendimethalin 30EC+Imazethapyr 2EC @1.0 kg ha-1 followed by manual hand weeding at 25-30 days after sowing which was closely followed by hand weeding twice at 20 and 40 days after sowing.